PENERAPAN BERMAIN SENSORIMOTOR DALAM MENINGKATKAN KONSENTRASI BELAJAR ANAK KELAS B2 TK KRISTEN DORKAS NUNHILA - Ina Lema Duan, Wilfrida; Novyani Seran, Theodorina; Ihzan Tajuddin, Al (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the implementation of sensorimotor play in improving the learning concentration of B2 class children at Dorkas Nunhila Christian Kindergarten. This study used a descriptive qualitative approach with teachers as the research subjects. Data were collected through observation, interviews, and documentation, while data analysis was carried out through data collection, data reduction, data presentation, and conclusion drawing using technique triangulation. The results showed that the implementation of sensorimotor play was carried out through three stages, namely planning, implementation, and evaluation. Planning was the process of preparing teaching modules systematically and purposefully as a guide for learning activities. Implementation was the process of applying all planned learning activities according to the intended objectives. Evaluation was conducted by the teacher through initial assessment, collecting children's work, anecdotal notes, and checklists. The implementation of sensorimotor play helped improve children's learning concentration so that children became more focused and able to participate in learning activities better.